High-Order Engineering Fastest Controller and Its Application in Thermal Power Units - Shangyao Shi; Jun Li; Yijia Huo; Ruiqi Li; Pengyun Chen (Energies)
In the domain of industrial process control, the ubiquitous proportional–integral–derivative (PID) control paradigm, while foundational, is deemed insufficient amidst evolving complexities. In alignment with China’s strategic “dual-carbon” targets, extant thermal power installations are mandated to facilitate profound peak load navigation and expedited frequency modulation services. The incumbent PID control schema is found wanting in this regard, precipitating the imperative for an innovative process control technology to supplant the conventional PID regimen. Power system engineers have consequently devised the engineering fastest controller (EFC), which has adeptly succeeded PID control in nascent applications, thereby meeting the stringent control exigencies for deep peak regulation and agile frequency modulation. Employing rigorous theoretical analysis and sophisticated simulation experiments, this investigation meticulously compares the performance attributes of high-order controllers (HOCs) with the EFC. The empirical findings underscore the EFC’s pronounced superiority over PI, PID, and SOC in regulatory performance enhancements by 122.2%, 88.0%, and 77.3%, respectively, and in mitigating disturbances by 140.0%, 80.9%, and 54.5%, respectively. This study culminates in the assertion that the EFC represents a paradigmatic advancement in industrial control technology, not only manifesting pronounced performance benefits but also furnishing a robust theoretical scaffolding that transcends the performance zeniths of traditional PID and HOC technologies.